As Simple as It Seems - Homer, Vincent (Proceedings of the Amsterdam Colloquium, 2011)
Even when linearized after it, seem can take scope above the modal can in configurations that involve a downward-entailing expression. Though it is tempting to regard this syntax-semantic mismatch as idiomatic, there are strong reasons to aim for a compositional analysis. Not least among these reasons is the unifying property of the triggers of the scope reversal, namely downward entailingness. The article claims that the main explanandum is the wide scope of seem not only over can, but also over the trigger. Reordering takes place, covertly: it is shown that seem is a mobile positive polarity item, which has the ability to raise above a potential anti-licenser. This movement permits aspectual configurations that are otherwise disallowed in the complement of seem. If it is on the right track, this analysis could pave the way for new insights on covert movement, complementation and subordinate tense.